The marketing analytics practitioner's guide volume 3 : digital marketing - Charan, Ashok (Singapore : World Scientific Publishing Co. Pte. Ltd., 2024)
"As the use of analytics becomes increasingly important in today's business landscape, The Marketing Analytics Practitioner's Guide (MAPG) provides a thorough understanding of marketing management concepts and their practical applications, making it a valuable resource for professionals and students alike. The four-volume compendium of MAPG provides an in-depth look at marketing management concepts and their practical applications, equipping readers with the knowledge and skills needed to effectively inform daily marketing decisions and strategy development and implementation. It seamlessly blends the art and science of marketing, reflecting the discipline's evolution in the era of data analytics. Whether you're a seasoned marketer or new to the field, the MAPG is an essential guide for mastering the use of analytics in modern marketing practices. Volume III is entirely dedicated to digital marketing. The first chapter, New Media, covers the impact of new media on the social, political and marketing landscape. It outlines the new rules and perspectives, leaving readers with a clear understanding of how they must adapt to succeed in the digital age. The Digital Marketing chapter covers a wide range of topics related to digital tools, techniques, processes, as well as the opportunities and challenges of digital marketing. A set of chapters on social media highlight best practices to adopt on each of the networks - Facebook, Twitter, Instagram, YouTube and LinkedIn. Search Engine Optimization (SEO) covers on-page and off-page optimization to increase inbound traffic and channel it through the digital marketing funnel. Web Analytics covers the processes that constitute a web analytics system and deals with the use of web analytics platforms such as Google Analytics to assess the effectiveness of digital marketing in attracting and converting prospects. Search Advertising covers advertising on search engines to draw prospects and lead them through the digital marketing funnel. It covers topics such as the Google auction, keyword strategies, and practices to improve the effectiveness of search advertising. The final chapter, Digital Execution, serves as a comprehensive guide to developing and executing digital marketing plans"--Provided by publisher.
Includes bibliographical references and index.
Keywords: Internet marketing